Evaluation of Geomorphological Landforms, Lineaments and Landuse/Landcover Using Geospatial Technologies in Parts of Nalgonda District, Telangana State, India. - M. Ganesh, K; Jagannadha Rao, M; Jai Sankar, G; S. S.Vara Prasad, A (International Journal of Engineering and Technology, 2018)
The present study is aimed to evaluate hydrogeomorphology, lineaments and landuse/landcover aspects of the study area using the IRS-IC & ID images. The false colour composition of IRS-IC & ID images are used for this study. It is advantageous to use satellite multispectral data as the image data in different bands can be exposed to digital improvement techniques. So the differences in objects can be highlighted to enhance the understanding of the image. Landforms are interpreted on the basis of interpretation element keys such as- tone, texture, size, shape, color etc. and extract the specific information from the false color composited LISS-III sensor images. Field observations showed that ground water occurs under unconfined conditions with water table at shallow to great depth. The lineament density map to be prepared to understand the impacts on groundwater percolation. The hydrogeomorphology, Lineament and Landuse/landcover maps are overlaid to trace groundwater potential zones. An integrated remote sensing and geographic Information System (GIS) based approach has been used for demarcating groundwater potential zones. Remote sensing techniques have been used to describe the hydrogeomorphology, land use / land cover and the lineaments of the study area using SPOT and IRS – I D visual products. Based on this the detailed descriptions of geomorphic features of the area are traced. Great emphasis is also given to the study of lineament pattern of the study area, the land use and land cover.